2022
DOI: 10.3389/fendo.2022.867838
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Obesity. Special Mention to Roux-en-Y Gastric Bypass and Vertical Gastrectomy

Abstract: IntroductionThe prevalence of obesity has increased exponentially in recent decades, being one of the diseases that most affects global health. It is a chronic disease associated with multiple comorbidities, which lead to a decrease in life expectancy and quality of life. It requires a multidisciplinary approach by a specialized medical team. Obesity can be treated with conservative or with surgical treatments that will depend on the characteristics of the patient.Objective/MethodologyThe referenced surgery ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 91 publications
1
10
0
2
Order By: Relevance
“…The mean age of the participants was 32.81 years; this was in accordance with the other study in Saudi Arabia when the mean age was 33.3 years(Alfadda et al, 2021), while it was younger than in the study in Norway(Järvholm et al, 2021). The age range in the current study was from 15 to 62 year, it was aligned with the internationally recommended age range for bariatric surgery of 18 to 65 years old(Luesma et al, 2022). According to our study, 16.1% of participants suffered from GERD following bariatric surgery, 32.7% were diagnosed with GERD before bariatric surgery and 51.2% of bariatric surgery patients were not diagnosed with GERD.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…The mean age of the participants was 32.81 years; this was in accordance with the other study in Saudi Arabia when the mean age was 33.3 years(Alfadda et al, 2021), while it was younger than in the study in Norway(Järvholm et al, 2021). The age range in the current study was from 15 to 62 year, it was aligned with the internationally recommended age range for bariatric surgery of 18 to 65 years old(Luesma et al, 2022). According to our study, 16.1% of participants suffered from GERD following bariatric surgery, 32.7% were diagnosed with GERD before bariatric surgery and 51.2% of bariatric surgery patients were not diagnosed with GERD.…”
supporting
confidence: 89%
“…A former Saudi Arabian study found an opposite finding, as there was no statistically noteworthy association with age, gender and diabetes as a chronic disease (p > 0.05), but it showed significant association with smoking (P=0.02) (Luesma et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…On the other hand, the hazard ratio for suicide was 2.4 times higher with surgery compared with non-surgery participants (95% CI: 1.57–3.68; p < 0.001), primarily in participants aged 18–34 years at surgery [ 79 ]. When choosing the most appropriate surgical technique, different factors must be taken into account, such as the primary aim of the treatment, the individual CV risk, the eventual digestive or esophago-gastric pathology, and the patient’s preference [ 81 ]. BS techniques can be classified as restrictive, malabsorptive, and mixed, based on the mechanism of action, as well as endoscopic or laparoscopic, based on the approach ( Table 3 ).…”
Section: Surgical Managementmentioning
confidence: 99%
“…Specifically, the laparoscopic vertical SG is a restrictive procedure that changes the gastric emptying, removing the fundus gastric, and dramatically reducing the production of ghrelin, having an additional anorectic action. On the contrary, RYGB is a mixed procedure: both restrictive, due to the small gastric pouch, and malabsorptive of sugars and fats, due to the bypass of the pancreatic duodenum that carries partially digested food to the distal intestine, thus improving glycemic balance [ 81 ]. A recently published meta-analysis in 114,919 patients did not find a clear effect of sex difference on the efficacy outcome of BS procedures, but men were more likely to achieve greater BMI loss, while women were 2.87 times more likely to be classified as weight responders (95% CI 1.90–4.34), with a higher percentage of excess weight loss, in particular after an intragastric balloon (0.72 95% CI: 0.42–1.02) [ 83 ].…”
Section: Surgical Managementmentioning
confidence: 99%
“…It represents the second most performed procedure [ 1 , 2 ]. This popularity is due to consistently satisfying and long-lasting weight loss and comorbidity resolution with acceptable complications and mortality rates [ 3 ]. Most patients expect to lose more than 70% of their excess weight in the first 12 months after the surgery.…”
Section: Introductionmentioning
confidence: 99%